ANALISIS PENERAPAN BIG DATA DALAM ADMINISTRASI SURAT MENYURAT: STUDI KASUS DI KANTOR DESA TELUKJAMBE KABUPATEN KARAWANG - Ersa Falena Fitri; Lukmanul Hakim; Kariena Febriantin; Fani Sahabi’ah (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
The implementation of governance and politics involves several essential components, including supervision, development empowerment, and public services. In this context, public service deliveryparticularly those related to matters of public interest, such as administrative management and correspondence deserves special attention. This study aims to analyze the application of big data in correspondence services at the Telukjambe Village Office. Using a qualitative approach through interviews, observations, and documentation, the study found that the use of information technology has not yet been fully optimized, with many procedures still carried out manually. This condition affects the efficiency and effectiveness of services and highlights the importance of utilizing existing and acquired data at the Telukjambe Village Office to ensure proper adherence to regulations.The findings reveal that the government apparatus at the Telukjambe Village Office has not yet achieved optimal performance in terms of service mechanisms, service efficiency, service accuracy, and staff competence in implementing technology. Several processes remain conventional, limiting the potential benefits of technological adoption. The lack of technology utilization results in slow recording and archiving processes, which are also vulnerable to data loss.Therefore, the development of a digital-based information system is urgently needed to enhance the quality of administrative services at the Telukjambe Village Office, making them more responsive, efficient, and transparent.